Nutritional value, bioactivity, and application potential of Jerusalem artichoke (Helianthus tuberosus L.) as a neotype feed resource - Yue Wang (Animal Nutrition, 2020)
The large-scale development of herbivorous animal husbandry in China has increased the demand for forage products. However, due to scarce land resources and poor soil quality, forage is in short supply. In particular, high-quality forage in China heavily relies on imports. The contradiction between supply and demand for forage grass products is increasingly notable. Therefore, the development of indigenous new forage resources with a strong ecological adaptability and a high nutritional value is a key to solving this problem. Jerusalem artichoke (JA, Helianthus tuberosus L.), a perennial herb of the genus Helianthus, has advantageous growth traits such as resistance to salinity, barrenness, drought, cold, and disease. The contents of crude protein, crude fiber, and calcium in the optimal harvest period of forage-type JA straw are comparable to those of alfalfa hay at the full bloom stage and the straw of ryegrass and corn at the mature stage. Inulin in JA tubers is a functional ingredient that has prebiotic effects in the gastrointestinal tract of monogastric animals and young ruminants. In addition, some bioactive substances (e.g. flavonoids, phenolic acids, sesquiterpenes, polysaccharides, and amino acids) in JA leaves and flowers have antibacterial, anti-inflammatory, and antioxidant functions as well as toxicities to cancer cells. These functional ingredients may provide effective alternatives to antibiotics used in livestock production. In this review, we summarized the potentials of JA as a feed ingredient from the aspects of nutritional value and fermenting characteristics of the straw, the functions of physiological regulation and disease prevention of inulin in the tubers, and bioactive substances in the leaves and flowers.